Prevalence of alcohol and substance use relapse in forensic inpatients with substance use disorders in Germany - Düger, Seyma; Sörensen, Finn; Völlm, Birgit (Frontiers in Psychiatry, 2025)
BackgroundOffenders who pose a risk of harm and whose convictions are linked to substance use can be mandated to undergo treatment in forensic psychiatric hospitals under Section 64 StGB of the German Penal Code (Strafsgesetzbuch; StGB), if there are reasonable prospects that treatment might be successful. Relapses during treatment is a common occurrence in patients with substance use disorders but little is known about the frequencies of such events in a forensic setting.PurposeThis study aimed to determine the prevalence of relapse among patients who undergo treatment under § 64 StGB, identify substances involved and possible predictive factors.MethodWe utilized data over the span of two years from 108 patients who were admitted to the Clinic of Forensic Psychiatry in Rostock, Germany, between 2019 and 2021.We used descriptive statistics and multiple regression analysis. A relapse was defined as a positive laboratory test for illicit drugs or alcohol, admission of relapsing or a declined test (i. e. the patient did not consent to the test).ResultsWe found that 65.7% of the patients relapsed within the initial two-year period of stay. Cannabinoids were the most commonly consumed substances. Factors such as age, education level, comorbidity, number of previous convictions, duration of stay and type of substance used did not significantly affect relapse rates. Results are limited by a small sample size.ConclusionA high relapse rate is still a reality of forensic addiction treatment. Static factors alone might only have a small predictive value for substance relapses and are not sufficient to fully predict individual risk. Therefore our findings show a need to focus on dynamic factors that affect consumption relapse rates. Considering the findings of this research, future studies should investigate dynamic factors of the patient’s substance use behavior during treatment as a whole (e.g. reason for relapsing, choice of drug etc.), identify and investigate other factors affecting relapse rate and uncover possible treatment interventions that might reduce relapse rates, dropout rates and criminal recidivism.